Role of body mass index and waist circumference in predicting of gestational diabetes mellitus, pregnancy induced hypertension and adverse pregnancy outcome amongst obese women - Anoohya, Bhukya; Grover, Suparna; Kaur, Amrit P.; Padda, Preeti; Kaur, Jagdeep (International Journal of Research in Medical Sciences, 2025)
Background: Risks to the pregnant women due to obesity during pregnancy include gestational diabetes, hypertensive disorders of pregnancy, sepsis, venous thromboembolism, stillbirth, preterm delivery, large for gestational age infant, cardiometabolic disease and obstructive sleep apnea. For the fetus, the risks include congenital anomalies, fetal growth restriction, macrosomia, prematurity, anomalies, and other adverse clinical outcomes. Thus, the aim of the present study was to the test hypothesis that waist circumference was as good as body mass index (BMI) to identify women at risk of obesity related complications during pregnancy. Methods: 200 pregnant women in first trimester of pregnancy coming in antenatal outpatient department (OPD) of government medical college, Amritsar were recruited from October 2022 to March 2024. Patients were classified as obese/non obese as per Asian ethnicity specific threshold of waist circumference according to which waist circumference ≥80 cm is obese. Based on BMI women were classified as underweight, overweight and obesity. Overweight is a BMI ≥25 kg/m2; and obesity is a BMI ≥30 kg/m2. Pregnancies were followed up throughout pregnancy and final outcome were recorded and compared. Results: Of the 200 participants, 13.5% were overweight, 4% were obese, another 10.5% were underweight and rest 72% had normal BMI. On the other hand, as per waist circumference the prevalence of obesity was 20% (waist circumference ≥80 cm), which was more than the combined prevalence (17.5%) of overweight (BMI=25-29.9) and obese (BMI ≥30) as per BMI. Both BMI >25 kg/m2 and waist circumference ≥80 cm are associated with increased odds of preterm labour gestational diabetes mellitus (GDM), hypertensive disorders of pregnancy (HDP), obstructed labour and SSI. It was statistically significant for GDM and HDP. Also, amongst women with >30 kg/m2 (obese), the odds of abortion and antepartum haemorrhage (APH) were increased significantly. Conclusions: Both high BMI and waist circumference/80 cm are significant risk factors for development of GDM and hypertension. Maternal obesity defined by BMI >30 is a significant risk factor for abortion and APH. These two complications are not predicted by waist circumference.